Biogeography of fire regimes in western U.S. conifer forests: A trait‐based approach. Issue 5 (5th March 2020) - Stevens, Jens T.; Kling, Matthew M.; Schwilk, Dylan W.; Varner, J. Morgan; Kane, Jeffrey M.
Abstract: Aim: Functional traits are a crucial link between species distributions and the ecosystem processes that structure those species' niches. Concurrent increases in the availability of functional trait data and our ability to model species distributions present an opportunity to develop functional trait biogeography (i.e., the mapping of functional traits across space). Functional trait biogeography can improve process‐based predictions about the resistance of certain species assemblages to changing environmental conditions across landscape scales. We illustrate this concept by developing the first trait‐based, quantitative ranking of fire resistance (adult tree survival) in North American conifer species and mapping that fire resistance across space. Location and time period: Western continental USA, present day. Major taxa studied: Twenty‐nine common conifer tree species. Methods: We compiled six traits for each species: three relating to tree morphology and three relating to litter flammability. We combined these traits into a single fire resistance score and used community‐weighted averaging to estimate the fire resistance scores of different forest communities, using interpolated species distribution and relative abundance data. Results: Species associated historically with frequent fire have high fire resistance scores (e.g., Pinus ponderosa ), reflected by thick bark, tall crowns and flammable litter. Species associated with subalpine or arid conditions have low fire resistance scores (e.g., Picea engelmannii and Pinus edulis ), reflected by thin bark, short stature, poor self‐pruning and low litter flammability. A map of forest community fire resistance across the western USA reveals agreement with independent assessments of historical fire regimes, while also identifying areas where community‐wide species traits might be mismatched with historical fire regimes. Main conclusions: Quantifying the functional traits that confer resistance to tree‐killing fire provides a direct link between ecosystem disturbance and community resistance. Understanding this link is crucial to evaluation of the long‐term resilience of different forest types under dynamic fire regimes. Our work represents the first known spatial representation of fire resistance traits at a regional scale and, as such, provides a link between functional traits and biogeography relevant to a critical ecosystem process.